Changes in purine levels associated with cellular brain injury in gerbils experimentally infected with Neospora caninum - Tonin A.A. (2014)
The present study was carried out in order to assess the possible alterations in purine levels of brain, associated neuronal lesions in gerbils experimentally infected with Neospora caninum. For that, gerbils (Meriones unguiculatus) were inoculated with Nc-1 strain of N. caninum, composing two different experiments: Experiment I (EI) and experiment II (EII), where purine levels were measured along with the histopathologic study, on days 7 (EI), 15 and 30 (EII), post-infection (PI). As a result, it was possible to observe that the purine levels (ATP, ADP, AMP, adenosine, inosine and xanthine) in brain in EI are significantly reduced (p < 0.05), while in EII we faced a different pattern, since in the majority the purine levels were significantly increased (p < 0.05) on days 15 (ATP, AMP, adenosine, hypoxanthine and xanthine) and 30 PI (ATP, ADP, AMP, adenosine, and uric acid). Results of brain histopathology did not show histological lesion in animals of EI; however, in gerbils of EII it was possible to verify that the alterations (lesions) were more pronounced in gerbils evaluated on day 30 PI when compared to day 15 PI. Therefore, it was possible to conclude that the purine levels in brain were altered in both experiments, concomitant with the histopathological injuries observed in EII. © 2014 Elsevier Ltd.